The Effect of Warm Red Ginger Water Foot Soaking Therapy on Blood Pressure of Hypertension Patients - Andry Sartika; Ira Tusan Suhada; Padila Padila (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of warm red ginger foot soak therapy on blood pressure among hypertensive patients in the working area of Jembatan Kecil Public Health Center, Bengkulu City. The research employed a quasi-experimental pre-post design involving both control and intervention groups. A total of 30 participants were selected using purposive sampling based on specific inclusion criteria. Statistical analysis revealed a significant p-value of 0.001 (p<0.05), indicating a meaningful reduction in blood pressure following the therapy The findings suggest that warm red ginger foot soak therapy has a significant effect on lowering blood pressure in hypertensive patients at Jembatan Kecil Public Health Center. It is recommended that the health center educate the community about the benefits and procedures of using warm red ginger foot soak therapy as a complementary approach to manage hypertension. Keywords: Warm Red Ginger Water, Hypertensive Patients. Blood Pressure